Hambatan Budaya Dalam Kesehatan Anak - Latifah, Latifah (Sunan Kalijaga State Islamic University & The Asia Foundation, 2006)
This article argues the cultural values have its potention as a hindrance of children health, both psychologically and physically. Cultural value that has its significant influence in children educational system is the perception and parental values of the parent in front of the children. Almost most of the parents are, generally, expecting their children's